2015
DOI: 10.1016/s1473-3099(15)00377-1
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma species in China

Abstract: Global feasibility assessment of interrupting the transmission of soil-transmitted helminths: a statistical modelling study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…Notably, extensive genetic variation was detected in msp2. Consistent with our results, sequence variation at the studied gene markers has been reported previously among isolates from ticks, sheep and goats [12,[15][16][17][18][20][21][22][23][24][25]. Similarly, genetic variation is common in other Anaplasma species [40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Notably, extensive genetic variation was detected in msp2. Consistent with our results, sequence variation at the studied gene markers has been reported previously among isolates from ticks, sheep and goats [12,[15][16][17][18][20][21][22][23][24][25]. Similarly, genetic variation is common in other Anaplasma species [40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 92%
“…Our genetic profiling results indicated that the newly generated 16S rRNA gene sequences shared a homology of > 99.5% with sequences of A. capra strains from humans, sheep, goats, cattle and ticks [12,15,16,18,20,22], suggesting that they likely are within the same species of bacteria [38,39]. Clustering of sequences named A. centrale from deer (Cervus nippon nippon) (GenBank: AB211164) and cattle (GenBank: AF283007) in Japan and from ticks (Haemaphysalis longicornis) in Korea (Gen-Bank: GU064903), as well as Anaplasma spp.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Anaplasma capra was initially found in asymptomatic goats, and case of human infection were confirmed in 2015 in Heilongjiang province, northern China [5]. The agent was also detected in Ixodes persulcatus in Heilongjiang province and Haemaphysalis longicornis ticks in Shandong Province [22]. The illness caused by A. capra are different from A. phagocytophilum infection [5].…”
Section: Resultsmentioning
confidence: 99%
“…Anaplasma capra has been identified in I. persulcatus and H. longicornis ticks in China [4, 16]. However, pathogen detection in arthropods is not sufficient to validate its vector competence.…”
Section: Discussionmentioning
confidence: 99%